Tinjauan Yuridis dan Dampak Hukum Kepada Pemegang Polis pada Likuidasi Perusahaan Asuransi yang Dicabut Izin Usahanya - Andri Kurniawan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Licensing gave the insurance company right to conduct its business activity, insurance company need to comply with provisions, one of the provision is corporate financial health. Failure to comply with the provisions will result in sanction in the form of company dissolution and liquidation. Shareholder conduct General Meeting of Shareholder (RUPS) to determine liquidation team. The company assets were blocked and seized by the state due to connection with other criminal cases. Failure in payment caused by the seizure made policy holder conduct litigation and non-litigation effort. This study aim to know and analyse the provisions regulation and supervision of the liquidation process that conducted by the company which license had been provoked. The second objectives are to know and analyse the impact to policy holders caused by the liquidation of PT Ausransi Jiwa Adisarana Wanaartha which had its business license revoked. The methodology that had been used in this study is normative legal research with approach based on legal principal, approach based on systemic approach to law, and approach based on synchronization to law. The result of this study is the legal basic regarding liquidation had not regulated adequately. Policyholders as the party that got the impact of the liquidation will be placed in a disadvantage condition due to the small return of payment from company asset, especially when insurance fund is not sufficient to cover all the obligated payment to policyholders.